Sexual and reproductive health awareness and practices among adolescents and adults in a rural farming community in Baja California, Mexico: a quantitative and qualitative cross-sectional study - Cristina Espinosa da Silva; Margarita Santibanez; Adrienne RS Lee; Lorena S Pacheco; Stephanie Brodine; Miguel A Fraga; Taylor B Desmarais; Noe C Crespo; Javier Martínez Hernandez; Marianne McKennett; Richard S Garfein (Sexual and Reproductive Health Matters)
Rural, indigenous populations in Mexico face barriers to accessing sexual and reproductive health (SRH) resources and services. Given the lack of information to inform educational materials tailored to the needs of these indigenous communities, we aimed to: (a) quantitatively characterise the SRH awareness and practices among adolescents and adults in a rural, mostly indigenous community in northern Mexico and (b) qualitatively assess community perspectives on an educational pamphlet with SRH information (e.g. contraceptive options). Quantitative data collection occurred in November 2018 and April 2019 using convenience sampling in a community clinic and random sampling for community households. Qualitative data collection occurred in November 2019 via individual interviews and focus group discussions to assess community perspectives about an SRH educational pamphlet developed from quantitative data. Participants in the quantitative phase of our study (n = 217) were a median age of 30 years, 71% were female, and those with children reported having a median of three (range = 1–11). SRH knowledge was low, as were self-reported efforts to obtain contraceptives or testing for HIV/STIs. Most believed that children should learn about SRH by age 10–15 years, and 94% felt that parents should deliver such education. Participants had low knowledge about SRH but high motivation to educate children and adolescents on these topics, indicating potential for SRH campaigns in this community. Health education materials were well-received in the qualitative phase of our study (n = 17 from individual interviews; n = 22 from focus group discussions), and raised interest among community members in learning more about these topics.